The 2006–2016 Translation Theory Development in Indonesian Universities: A Corpus-Based Study - Dewi, Haru Deliana; Pamungkas, Muhammad Ersan; Hidayat, Rahayu Surtiati (Paradigma: Jurnal Kajian Budaya, 2019)
This paper reviews the theories used by new scholars in Translation Studies (TS) in Indonesia, to determine whether TS or translation theory there has followed the development of TS throughout the world. The study investigated the terms and authors/ scholars of TS found in the final papers of students at Universitas Indonesia and Universitas Negeri Jakarta between 2006 and 2016. Using a corpus tool, WordSmith Tools 6.0, keyword and cluster analyses were applied to search for terms and authors. Results show no significant progress in attainment of knowledge on TS. Indonesian students’ knowledge of translation theory seems to come primarily from the 1960s–1990s era.